A bibliometric analysis corporate university discourse - Savitri, Renny; Samsara, Ladiatno; Cahyarini, Benedicta Retna; Ahad, Madya Putra Yaumil; Gusparirin, Rori; Firmansyah, Nurhuda (Berkala Ilmu Perpustakaan dan Informasi, 2024)
Introduction This research investigate scientific publication trends related to corporate university themes. All publications are indexed in the Scopus database from the first publication until April 2022. Limited discussion of corporate university using bibliometric analysis in Scopus is the novelty of this paper. Data Collection Methods Using bibliometric analysis with data visualization performed with VOS viewer application version 1.6.18 Results and Discussion.. The first publication related to the corporate university theme emerged in 1985 and reached its peak in 2017, then tended to decrease until April 2022. The US is the most influential country in the corporate university theme in both the number of publications and number of citations. Intellectual Partnership Consulting from the UK is the most influential organization with the highest number of publications. Whereas Chairman of Paradigm Shift International contribute as the most cited publication. Conclusion. "Corporate University" has become an interesting research theme in HR development for the last four decades. It is shown from the increase of the publication numbers and authors from various organizations accros the world. Furthermore, the authors’ perspective in terms of corporate university varies. The study should inform researchers, practitioners and policy makers to improve and enhance corporate university governance.